1995
DOI: 10.1007/bf00352225
|View full text |Cite
|
Sign up to set email alerts
|

Polytene chromosomes show normal gene activity but some mRNAs are abnormally accumulated in the pseudonurse cell nuclei of Drosophila melanogaster otu mutants

Abstract: Certain mutant alleles of the ovarian tumor (otu) locus give rise to polytene chromosomes in the pseudonurse cells (PNCs). We have previously shown that the banding pattern of these germ line-derived chromosomes is similar to that in the larval salivary gland chromosomes. In this study, we have examined the gene activity of these chromosomes. General gene expression from these chromosomes was studied by uridine autoradiography. The expression of specific genes was monitored by in situ hybridisation to mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Similar defects in nurse cell nuclei decondensation have not been reported in DNA replication mutants but have been reported in numerous female-sterile mutations such as ovarian tumor (otu), string of pearls (sop), squid (sqd), tulipano (tlp), morula (mr), and rhino (rhi) (Cramton and Laski 1994;Heino et al 1995;Reed and Orr-Weaver 1997;Gigliotti et al 1998;Volpe et al 2001;Goodrich et al 2004). Rhino is of particular interest; it is a female-specific HP1-like chromodomain protein that has been postulated to modulate chromosome structure at the end of endo- cycle 5 (Volpe et al 2001).…”
Section: Discussionsupporting
confidence: 62%
“…Similar defects in nurse cell nuclei decondensation have not been reported in DNA replication mutants but have been reported in numerous female-sterile mutations such as ovarian tumor (otu), string of pearls (sop), squid (sqd), tulipano (tlp), morula (mr), and rhino (rhi) (Cramton and Laski 1994;Heino et al 1995;Reed and Orr-Weaver 1997;Gigliotti et al 1998;Volpe et al 2001;Goodrich et al 2004). Rhino is of particular interest; it is a female-specific HP1-like chromodomain protein that has been postulated to modulate chromosome structure at the end of endo- cycle 5 (Volpe et al 2001).…”
Section: Discussionsupporting
confidence: 62%
“…Heino et al [1995] have performed in situ hybridizations to identify mRNAs in the ovaries of otu 7 homozygotes. Messenger RNAs encoded by the genes ovo, otu, bcd, and pum were observed to be bound to localized regions of polytene chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Since Drosophila nurse cells with polytene chromosomes can often function normally, we suggested that term ''pseudonurse'' be used only for those cells that resemble NCs but are not a part of a nurse cell/oocyte syncytium. Heino et al [1995] have performed in situ hybridizations to identify mRNAs in the ovaries of otu 7 homozygotes. Messenger RNAs encoded by the genes ovo, otu, bcd, and pum were observed to be bound to localized regions of polytene chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation